Signaling pathways of β-cell death in type 2 diabetes mellitus: the role of innate immunity - Zilya. A. Kalmykovа; Irina V. Kononenko; Olga M. Smirnova; Marina Vladimirovna Shestakova (Сахарный диабет)
Type 2 diabetes mellitus (T2DM) is a multifactorial metabolic disease, the development of which is mediated by both genetic disorders and various intracellular and extracellular molecular processes. One of the main pathogenetic mechanisms for the development of T2DM is a progressive decrease in the mass and functional reserve of β-cells, which largely determines the course of T2DM. The mechanisms of action of most sugar-lowering drugs are associated with increased secretion of insulin, so it is obvious that the effectiveness of the therapy will also largely depend on the functional state of β-cells. All this explains the great interest in studying the mechanisms of damage of β-cells in T2DM and factors that can accelerate this process, leading to their death and the development of a relative and then absolute insulin deficiency. The mechanisms of dysfunction β-cells in T2DM have not been studied much. This article provides an overview of the data of domestic and foreign literature of recent years on the molecular, intracellular features of various mechanisms of damage and death of β-cells in type 2 diabetes. The results of studies aimed at studying the possible factors and processes leading to their launch are presented.